Strategi Penjualan dan Distribusi pada UMKM Alam Flora Sejahtera - Elsa Rahmadani; Nafisa Naila Husna; Oki Anggraeni; Dijan Rahajuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to identify sales and distribution strategies to improve the competitiveness of Alam Flora Sejahtera's MSMEs. The research object focuses on MSMEs engaged in the sale of natural fertilizers, planting media, and plant equipment. This study used qualitative methods with data collection techniques through observation, interviews, and documentation. The results show that Alam Flora Sejahtera's MSMEs have implemented a sales strategy that combines direct sales and sales through digital platforms such as WhatsApp, Instagram, and Google. The use of digital media has been proven to increase consumer reach and business visibility. In addition, the distribution system is carried out directly to consumers so that product and service quality is better maintained. However, inconsistent digital promotion management, high shipping costs, and increasingly fierce business competition still hinder optimal business competitiveness. Therefore, a more integrated sales and distribution strategy is needed so that MSMEs can maintain their business sustainability.